Restorative justice approach in resolution of criminal cases of blasphemy committed by health care workers in bathing covid-19 body at djasemen regional general hospital, Pematangsiantar - Lailatus Sururiyah (Indonesian Journal Education, 2026)
During the COVID-19 pandemic, the concept of restorative justice emerged as a potentially ideal approach for law enforcement and conflict mitigation. One notable case occurred at Djasamen Saragih Regional General Hospital in Pematangsiantar, involving the washing of the body of a woman confirmed to have COVID-19 by four male healthcare workers. In response to this case, the Pematangsiantar District Attorney’s Office decided to discontinue the prosecution by issuing a Decree on Termination of Prosecution (Surat Ketetapan Penghentian Penuntutan / SKP2) Number D-505/L.12/Eku/02/2021. This decision can be regarded as appropriate and proportionate under the circumstances. The Head of the Pematangsiantar District Attorney’s Office, Agustinus, stated that the four healthcare workers were not proven to have violated Article 156a in conjunction with Article 55 of the Indonesian Criminal Code concerning blasphemy.